Pemberian Sanksi Pidana Bagi Pelaku Penyebaran Hoax Ditinjau Dari Aspek Tindak Pidana Terorisme - Afdal Junaidi; Triono Eddy; Alfi Sahari (Journal of Education, Humaniora and Social Sciences (JEHSS), 2020)
This research, descriptive analysis, with a statutory approach, conseptual approach. The purpose of this research is to analyze the from of spreading fake news in Indonesia legislation and criminal sactions for the perpetrators of spreading fake news in term of the criminal act of terrorism. The results of this study indicate that the form of spreading fake news can be categorized as criminal act of terrorism, where the criminal act of terrorism is also threatening the safety of the nation and the state, causing divisions, causing uproar in the community, even though the act of spreading fake news is not regulated in the terrorism law but causes the effect that may be the same as that of terrorism, it’s just that the act of spreading fake news does not threaten the lives of many people. Whereas the criminal sanction for the perpetrators of spreading fake news inthe terms of the aspect of the criminal act of terrorism are equivalent to the convictions of criminal conspiracy, attempted and assisting in committing the crime of terrorism.